Mapping the Competitive Advantage of SMEs in East Java, Indonesia - Tobing, Diana Sulianti K.; Fathorazz, Moehammad; Wulandari, Gusti Ayu (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2018)
This article describes the situation and potential of SMEs in East Java Indonesia. Small and medium enterprises are essential to support the economic progress of a country. By using descriptive analysis and multiple regression then generated mapping. Mapping the characteristics and competitiveness of SMEs is done as a basis for gap analysis. If the current condition of Indonesian SMEs is known, benchmarking can be done by comparing ideal conditions or targets to be achieved in the face of global competition. The mapping generated from this research is expected to provide an overall picture of SMEs in disrict of Jember, Bondosowo, Situbondo and Banyuwangi, East Java Province, Indonesia, so that it can assist government and business actors in determining business strategies and policies. This study found the variables that significantly affect the competitive position are innovation ability, quality focus, customer loyalty, response to change, price advantage and marketing power. While the insignificant membership of the cooperative, it does not have a significant role for the creation of a strong competitive position. This is supported by the fact that most of the SMEs in eastern Java are not members of the cooperative. Similarly, business status with legal status and not and the use of intermediary traders is not a thing that affects the strength of competitive position.